The Mediating Role of Attitude and Perceived Usefulness in the Relationship between Direct Marketing, Perceived Trust, Perceived Ease of Use, and Purchase Intention - Golan Hasan; Erni Erni (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aimed to examine the impact of perceived trust and perceived ease of use on purchase intent, considering the mediating roles of attitude and perceived usefulness. The research employed a sample of 350 respondents from employees and consumers of Hong Yi Indonesia Ltd in Batam City, utilizing questionnaire distribution and SmartPLS application for data analysis. The findings revealed significant effects of perceived trust, perceived ease of use, and perceived usefulness on purchase intention. Interestingly, attitude was found to have no direct influence on purchase intention, and it did not mediate the relationship between perceived trust and purchase intention. However, perceived usefulness was identified as a mediator in the connection between perceived ease of use and purchase intention. Moreover, perceived trust was shown to impact attitude, while perceived ease of use influenced perceived usefulness. These results provide valuable insights for companies seeking to enhance consumer purchase intent, emphasizing the importance of trust, ease of use, and perceived usefulness in shaping attitudes and driving purchasing decisions. Companies can utilize these findings for assessment and strategic development, aiming to optimize various aspects of their business to attract and retain consumers.